Pengaruh Konseling Antenatal terhadap Penerimaan AKDR pascasalin sebuah uji klinis non randomisasi - Faris, Abdul; Soetrisno, Soetrisno; Siswosudarmo, Risanto; Malinta, Umar (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2018)
Background: During postpartum period women have a high motivation to start using contraception and postpartum IUD is an ideal method to offer. The rate of IUD use is still low, 14.06% of all postpartum contraceptive use. This might be attributed to lack of information and counseling from health providers.Objective: To compare the number of postpartum IUD used among groups of clients who were counseled during ANC and re-counseled during latent phase (exposed group), and group counseled during latent phase only (control group).Method: This study was a prospective quasi-experimental or randomised clinical trial. The first group was those counseled during ANC and latent phase, and the second was those counseled at latent phase only. Chi square and relative risk were used for statistical test two proportions.Result and Discussion: A total of 342 subjects who met inclusion and exclusion criteria were recruited. They consisted of the 210 subjects (61,4%) for the first group and 132 subjects (38,6%) for the second.The rate of IUD used in the first group was 82 of 210 (39%) and 30 of 132 (22.7%) in the second, RR 1,72 (95% CI 1.20 – 2.46), p 0,002. The rate of IUD used was also significantly influenced by a history of IUD acceptor RR 2,90 with 95% CI 2.23 – 3.77), a history of contraceptive used (RR 1,79 with95% CI 1,18 – 2,71) and a history of contraceptive counselling (RR 1,50 with 95% CI 1,03 – 2,19).Conclusion: Clients who were counseled twice (during ANC and repeated at latent phase) had higher rate of postpartum IUD used significantly than those who were counseled at latent phase only. Other factors that significantly affected the rate of postpartum IUD used were history of IUD acceptor, history of contraceptive used.Keywords: Postpartum IUD; counseling; rate of postpartum IUD use; antenatal care